DAO as digital governance tool for collaborative housing - Lustenberger, Michael; Wollenschläger, Sabrina; Küng, Lukas (Frontiers in Blockchain, 2025)
This paper explores the promise of decentralized autonomous organizations (DAOs) as a digital governance tool for collaborative housing initiatives. Based on existing literature around the collaborative housing initiative no1s1, we explore the research question: How can DAOs help govern collaborative housing initiatives? To address this, we employ conceptual research methods, synthesizing theories from the field of collaborative housing and DAOs to propose a new framework for the governance of such initiatives. Our analysis identifies five key benefits of DAOs in collaborative housing governance: a transparent crypto-accounting system, scalable decision-making, global jurisdiction and rule enforcement, automated rights and incentives system, and flexible polycentric governance. These benefits align with Elinor Ostrom’s “Governing the Commons” principles and highlight the potential of DAOs to enable scalability and autonomy in geographically dispersed communities. While theoretical, our study provides insights into the transformative potential of blockchain-based DAOs in collaborative housing governance, laying the groundwork for further research and real-world and empirical validation.